Differential gene expression in notochord and nerve cord fate segregation in the Ciona intestinalis embryo. Issue 9 (12th August 2013) - Kobayashi, Kenji; Yamada, Lixy; Satou, Yutaka; Satoh, Nori
<x xml:space="preserve">Abstract</x> During early embryogenesis, embryonic cells gradually restrict their developmental potential and are eventually destined to give rise to one type of cells. Molecular mechanisms underlying developmental fate restriction are one of the major research subjects within developmental biology. In this article, this subject was addressed by combining blastomere isolation with microarray analysis. During the 6th cleavage of the Ciona intestinalis embryo, from the 32‐cell to the 64‐cell stage, four mother cells divide into daughter cells with two distinct fates, one giving rise to notochord precursor cells and the other to nerve cord precursors. Approximately 2, 200 each of notochord and nerve cord precursor cells were isolated, and their mRNA expression profiles were compared by microarray. This analysis identified 106 and 68 genes, respectively, that are differentially expressed in notochord and nerve cord precursor cells. These included not only genes for transcription factors and signaling molecules but also those with generalized functions observed in many types of cells. In addition, whole‐mount in situ hybridization showed dynamic spatial expression profiles of these genes during segregation of the two fates: partitioning of transcripts present in the mother cells into either type of daughter cells, and initiation of preferential gene expression in either type of cells. genesis 51:647–659. © 2013 Wiley Periodicals, Inc.